Optimizing Doses of Ceftolozane/Tazobactam as Monotherapy or in Combination with Amikacin to Treat Carbapenem-Resistant Pseudomonas aeruginosa - Worapong Nasomsong; Parnrada Nulsopapon; Dhitiwat Changpradub; Supanun Pungcharoenkijkul; Patomroek Hanyanunt; Tassanawan Chatreewattanakul; Wichai Santimaleeworagun (MDPI AG, 2022)
Carbapenem-resistant Pseudomonas aeruginosa (CRPA) is a hospital-acquired pathogen with a high mortality rate and limited treatment options. We investigated the activity of ceftolozane/tazobactam (C/T) and its synergistic effects with amikacin to extend the range of optimal therapeutic choices with appropriate doses. The E-test method is used to determine in vitro activity. The optimal dosing regimens to achieve a probability of target attainment (PTA) and a cumulative fraction of response (CFR) of ≥90% were simulated using the Monte Carlo method. Of the 66 CRPA isolates, the rate of susceptibility to C/T was 86.36%, with an MIC50 and an MIC90 of 0.75 and 24 µg/mL, respectively. Synergistic and additive effects between C/T and amikacin were observed in 24 (40%) and 18 (30%) of 60 CRPA isolates, respectively. The extended infusion of C/T regimens achieved a ≥90% PTA of 75% and a 100% fT > MIC at C/T MICs of 4 and 2 µg/mL, respectively. Only the combination of either a short or prolonged C/T infusion with a loading dose of amikacin of 20-25 mg/kg, followed by 15-20 mg/kg/day amikacin dosage, achieved ≥90% CFR. The C/T infusion, combined with currently recommended amikacin dose regimens, should be considered to manage CRPA infections.